Left Atrial Appendage Closure for Stroke Prevention in Patients with Atrial Fibrillation and Hereditary Hemorrhagic Telangiectasia - Sebastiaan Velthuis; Martin J. Swaans; Johannes J. Mager; Benno J. W. M. Rensing; Lucas V. A. Boersma; Martijn C. Post (Case Reports in Cardiology)
Atrial fibrillation (AF) is the most common cardiac arrhythmia, affecting millions of individuals worldwide, and a major risk factor for disabling cerebral embolic stroke. Hereditary hemorrhagic telangiectasia (HHT) is an autosomal dominant inherited disorder, characterized by vascular abnormalities with high-bleeding tendency and therefore intolerance for oral anticoagulation. We report a case of percutaneous closure of the left atrial appendage, which might be a good alternative strategy instead of chronic oral anticoagulation to protect patients with high-risk AF and HHT from cerebral embolic strokes.